Electrospinning Hetero‐Nanofibers of Fe3C‐Mo2C/Nitrogen‐Doped‐Carbon as Efficient Electrocatalysts for Hydrogen Evolution. Issue 12 (12th June 2017) - Lin, Huanlei; Zhang, Wenbiao; Shi, Zhangping; Che, Minwei; Yu, Xiang; Tang, Yi; Gao, Qingsheng
Abstract: Invited for this month′s cover is the group of Qingsheng Gao at Jinan University. The image shows the synergistically improved kinetics on Fe3 C‐Mo2 C hetero‐interfaces for hydrogen evolution, as illustrated by the easily passed hurdles in hurdle race. The Full Paper itself is available at10.1002/cssc.201700207 . Abstract : "The meteoric particles stride the hurdles toward the bright future…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201700207 . View the Front Cover here:10.1002/cssc.201700832 .